A tendency towards leaf rust resistance decrease in common wheat introgression lines with genetic material from Aegilops speltoides Tausch - L. Ya. Plotnikova; L. V. Meshkova; E. I. Gultyaeva; O. Р. Mitrofanova; I. F. Lapochkina (Вавиловский журнал генетики и селекции)
Leaf rust, caused by the fungus Puccinia triticina Erikss., inflicts serious crop loss of common wheat Triticum aestivum L. The species Aegilops speltoides Tausch (2n = 14, SS) is considered a promising issue of genes to protect bread wheat from diseases. The objective of this study was the monitoring of resistance to leaf rust of Ae. speltoides accessions and introgressive lines and cultivars with genetic material of this species to the Western Siberian population of fungus. The estimation of specimens in the field conditions on natural infectious background showed that the Ae. speltoides accessions were immune to leaf rust, however, а tendency towards increasing susceptibility of the introgressive lines and varieties was detected. The protective effect of the known genes Lr28, Lr36 and Lr35 decreased, but Lr47 remained efficient in West Siberia, as confirmed by the results of testing of the Omsk population of P. triticina for virulence to the mentioned genes. During the study (2003-2017) the resistance has been overcome of lines Od 26/89, 156/90, analogs of cv. Novosibirskaya 67 – ANK-39 (B, C), and L-500 from the “Arsenal” сollection. High resistance to leaf rust was preserved of lines Od (35/1, 35/89, 210/90, 278/89); ANK39 (A, D, E); L-501 and cvs. Chelyaba 75 and Mit. Analysis of DNA markers and phytopathological tests showed that the studied varieties and lines lacked the known genes Lr28, Lr36, and Lr47 from Ae. speltoides (except for the lines of cvs. Thatcher and Pavon). On the base of analysis of DNA markers, it was assumed that Chelyaba 75 and seven resistant lines from the Odand ANK-39-series have translocations bearing the LrSp gene. Presumably, the rest of samples possess additional not yet identified genes of Ae. speltoides. The trend of overcoming of resistance to leaf rust of introgressive lines and varieties with Ae. speltoides genes should be taken into consideration in common wheat breeding in Western Siberia.